Rethinking a place for change: an architectural interpretation of the incarcerated youth's place for treatment - Verme, Martina (My University, 2022)
The Swedish National Board of Institutional Care is envisioned to be “a place for change” - giving individually adapted care and better conditions for a functioning life of youths in compulsory care. However, the dual tasks of treating and guarding present the challenge of developing the physical environment since it is a key factor for enabling receptivity to care. Research shows that the physical environment is linked to negative connotations within today’s society including stigmatization, negative self-image, and actions within the youth’s lifeworld, often resulting in unsuccessful readaptation. The thesis aims from the youth perspective to rethink the youth’s place for treatment within compulsory care. This is done by extracting and clarifying its role within the organization, at the institutional site and in the space for care. The project contains three connected parts. Firstly, applied research of the youth’s subjective experience of socio-spatial concepts in relation to being “in place” for care, as well as the field of Evidence-based healthcare design with a focus on psychiatry, collecting spatial aspects. Secondly, a concluded framework with general recommendations for the development of a treatment facility, which is then used to present the third part: a final design proposal applied to a certain institutional site. This way, the architectural process explores the potential role of a future treatment facility acting on the border of the institutional sphere. Both motivational and preventative design methods carry this exploration resulting in a new treatment facility that could ease residential facilities with the intention to provide a clear chain- and centre of care as a key towards an exit. The project is presented from four identified spatial perspectives that support the youth needs, contributing to knowledge development that supports the incarcerated youth exit process. The framework also complements the participatory process, which is currently complex and sensitive to set up due to an inaccessible user group. Thus, this becomes one of many investigations developing an evidence-based starting point for design decisions. Finally, it informs a preventative approach toward youth criminality while shifting the prioritization and presumptions of youth needs within the institutions. We need to ask ourselves, what does a place for change really mean for the youths themselves?
Keywords: Compulsory youth care, Socio-spatial experience, Place for treatment